Development and Validation of a RP-HPLC Method for Quantitative Analysis of Linagliptin in Bulk and Dosage Forms (Dhaka University Journal of Pharmaceutical Sciences, 2018)
This research was aimed to establish a versatile, sensitive, rapid and validated RP-HPLC method to analyze linagliptin in bulk as well as in pharmaceutical dosage forms. Liquid chromatography was performed on HPLC system and 20μl of samples were injected into a C18 column (150 x 4.6 mm i.d., 5μm particle size) and the eluents were monitored through a PDA detector at 239 nm. An isocratic method with a flow rate of 1 ml/min was used to elute the compounds with a mobile phase comprised of 70:30 v/v mixture of phosphate buffer (pH 6.8±0.2) and acetonitrile. The retention time of the compound was found to be 2.8 minutes. According to the ICH Q2(R1) guidelines, the method was validated by establishing several analytical parameters such as system suitability, specificity, linearity, accuracy, precision, limit of detection (LOD), limit of quantitation (LOQ), ruggedness and robustness to assay linagliptin. The method showed good linearity (R2 = 0.9981) over the concentration ranges of 40 – 60 μg/ml with a recovery between 99.48% ± 0.38% RSD to 100.22% ± 0.011% RSD, whereas the LOD and LOQ values were 0.05 μg/ml and 0.15 μg/ml, respectively. The relative standard deviation (% RSD) for inter-day and intra-day precision was not more than 2.0%. Hence, the proposed method can be applied accurately for research and routine analysis of linagliptin in bulk as well as different pharmaceutical dosage forms.Dhaka Univ. J. Pharm. Sci. 17(2): 175-182, 2018 (December)